2011
DOI: 10.3171/2011.8.jns11105
|View full text |Cite
|
Sign up to set email alerts
|

Is postoperative intensive care unit admission a prerequisite for elective craniotomy?

Abstract: Routine ward admission for patients undergoing elective craniotomies with selective ICU admission appears safe; however, approximately 2% of patients may require a direct postoperative unplanned ICU admission. Patients with anticipated long operation times, extensive blood loss, and high anesthetic risks should be selected for postoperative ICU admission, but further study is needed to determine the preoperative factors that can aid in identifying and caring for these groups of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 12 publications
2
71
0
1
Order By: Relevance
“…Beauregard and Friedmann 6 reported that 2 of 132 patients required ICU admission from the floor after craniotomy. Similarly, Bui et al 5 reported 10 response calls among 343 elective craniotomy patients, none of which resulted in ICU transfer. Clearly, patients with some neurologic interventions can be safely observed in a general ward, and the safety of this practice among patients undergoing elective aneurysm treatment is shown for the first time in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beauregard and Friedmann 6 reported that 2 of 132 patients required ICU admission from the floor after craniotomy. Similarly, Bui et al 5 reported 10 response calls among 343 elective craniotomy patients, none of which resulted in ICU transfer. Clearly, patients with some neurologic interventions can be safely observed in a general ward, and the safety of this practice among patients undergoing elective aneurysm treatment is shown for the first time in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on neurosurgical patients after craniotomy have suggested that ICU care after craniotomy may not be necessary. 5,6 Zimmerman et al 7 conducted a multicenter analysis of 3000 patients admitted to ICU care for neurosurgical diseases and found that among patients who were only observed in the ICU, Ͻ10% were likely to need any ICU treatments. Their analysis highlighted the need for comprehensive admission guidelines to the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies from different practices are needed to establish predictive factors to preoperatively and intraoperatively identify patients who would benefit from selective ICU admission. 5,9,54 In Group 3 in the present study, safe orientation of selected patients to more cost-efficient bed allocations contributed to significant cost reductions.…”
Section: Targeting Bed Assignmentmentioning
confidence: 86%
“…26 Recently, studies have documented the safety and feasibility of direct ward admissions for patients undergoing elective craniotomies, reserving ICU admissions for selected patients needing intensive care. 9,51,54 As ICU resources become more limited, this paradigm change will become more prevalent. In the present study, the care for most patients in the ICU consisted of intense monitoring, not intense care, except for one patient who developed postoperative parotitis and needed reintubation for airway protection within 4-6 hours after arrival in the ICU.…”
Section: Targeting Bed Assignmentmentioning
confidence: 99%
“…The most feared complications after craniotomy are intracranial hematoma formation on the surgical site and cerebral edema as a result of surgical trauma, leading to an increase in intracranial pressure. (5)(6)(7)(8)(9)(10) The performance of a bedside neurological examination is one of the possible evaluations for early detection of intracranial hypertension.…”
Section: %mentioning
confidence: 99%